Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To solve the system of linear equations
[tex]\[ \begin{cases} 4x - 3y = 7 \\ 5x - 2y = 0 \end{cases} \][/tex]
we will solve it step-by-step.
### Step 1: Write the equations
1. [tex]\( 4x - 3y = 7 \)[/tex]
2. [tex]\( 5x - 2y = 0 \)[/tex]
### Step 2: Solve one of the equations for one variable
From the second equation:
[tex]\[ 5x - 2y = 0 \][/tex]
Solve for [tex]\( x \)[/tex]:
[tex]\[ 5x = 2y \][/tex]
[tex]\[ x = \frac{2}{5}y \][/tex]
### Step 3: Substitute [tex]\( x \)[/tex] into the first equation
Now, substitute [tex]\( x = \frac{2}{5}y \)[/tex] into the first equation:
[tex]\[ 4 \left(\frac{2}{5}y\right) - 3y = 7 \][/tex]
[tex]\[ \frac{8}{5}y - 3y = 7 \][/tex]
### Step 4: Simplify and solve for [tex]\( y \)[/tex]
[tex]\[ \frac{8}{5}y - \frac{15}{5}y = 7 \][/tex]
[tex]\[ \frac{8 - 15}{5}y = 7 \][/tex]
[tex]\[ \frac{-7}{5}y = 7 \][/tex]
Multiply both sides by [tex]\( -\frac{5}{7} \)[/tex]:
[tex]\[ y = 7 \times -\frac{5}{7} \][/tex]
[tex]\[ y = -5 \][/tex]
### Step 5: Substitute [tex]\( y \)[/tex] back into the equation for [tex]\( x \)[/tex]
Using [tex]\( y = -5 \)[/tex] in [tex]\( x = \frac{2}{5}y \)[/tex]:
[tex]\[ x = \frac{2}{5}(-5) \][/tex]
[tex]\[ x = -2 \][/tex]
### Conclusion
The solution to the system of equations is [tex]\( x = -2 \)[/tex] and [tex]\( y = -5 \)[/tex].
[tex]\[ \begin{cases} 4x - 3y = 7 \\ 5x - 2y = 0 \end{cases} \][/tex]
we will solve it step-by-step.
### Step 1: Write the equations
1. [tex]\( 4x - 3y = 7 \)[/tex]
2. [tex]\( 5x - 2y = 0 \)[/tex]
### Step 2: Solve one of the equations for one variable
From the second equation:
[tex]\[ 5x - 2y = 0 \][/tex]
Solve for [tex]\( x \)[/tex]:
[tex]\[ 5x = 2y \][/tex]
[tex]\[ x = \frac{2}{5}y \][/tex]
### Step 3: Substitute [tex]\( x \)[/tex] into the first equation
Now, substitute [tex]\( x = \frac{2}{5}y \)[/tex] into the first equation:
[tex]\[ 4 \left(\frac{2}{5}y\right) - 3y = 7 \][/tex]
[tex]\[ \frac{8}{5}y - 3y = 7 \][/tex]
### Step 4: Simplify and solve for [tex]\( y \)[/tex]
[tex]\[ \frac{8}{5}y - \frac{15}{5}y = 7 \][/tex]
[tex]\[ \frac{8 - 15}{5}y = 7 \][/tex]
[tex]\[ \frac{-7}{5}y = 7 \][/tex]
Multiply both sides by [tex]\( -\frac{5}{7} \)[/tex]:
[tex]\[ y = 7 \times -\frac{5}{7} \][/tex]
[tex]\[ y = -5 \][/tex]
### Step 5: Substitute [tex]\( y \)[/tex] back into the equation for [tex]\( x \)[/tex]
Using [tex]\( y = -5 \)[/tex] in [tex]\( x = \frac{2}{5}y \)[/tex]:
[tex]\[ x = \frac{2}{5}(-5) \][/tex]
[tex]\[ x = -2 \][/tex]
### Conclusion
The solution to the system of equations is [tex]\( x = -2 \)[/tex] and [tex]\( y = -5 \)[/tex].
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.